Does Foreign Direct Investment Transfer Technology Across Borders? A Reexamination - Jürgen Bitzer; Monika Kerekes (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2005)
Reexamining foreign direct investment (FDI) as a potential channel for knowledge diffusion - based on industry data from seventeen OECD countries during the period 1973-2000 - we find that FDI-receiving countries benefit strongly from FDI-related knowledge spillovers. We do not find evidence for positive FDI-related technology sourcing effects. Instead, our results suggest that outward FDI might have negative effects on the output of the FDI- sending country.
Keywords: O47; O33; E23; F21; 330; foreign direct investment; knowledge spillovers; Direktinvestition; Technologietransfer; Wissenstransfer; OECD-Staaten